A techno-commercial decision support framework for optimal district cooling system design in tropical regions. (5th February 2023) - Zaw, K.; Kwik, Z.Z.S.; Chang, W.Q.; Islam, M.R.; Poh, T.K.
Highlights: A techno-commercial framework for district cooling systems engaging optimization. Established a cost function employing technical and commercial relationships. Proposed a district cooling system design optimisation with established cost function. Conducted a case study and achieved promising results offering the optimal design. Achieved life cycle cost saving up to 21% and a 20% shorter payback period. Abstract: For tropical climates with high cooling demands, the district cooling system is recognised as a viable cooling solution for efficient utilisation of energy and its assets. It is imperative to develop a technically and commercially optimised district cooling system analysis that is rarely reported. This paper presents a hybrid design strategy of actual scale district cooling system by considering the interdependent influences of the technical, investment and operational parameters. Firstly, the cooling demand of a typical district cooling system is mathematically formulated. The technical parameters such as cooling energy production capacity and thermal energy storage capacity are closely related to the commercial parameters known as operations, maintenance and investment cost over the whole economic life cycle. The relationships among 14 technical and commercial parameters are established, and a cost function is proposed. Finally, the interior point method is adopted for the financially and operationally optimised district cooling system design. The developed optimal design approach is applied to a district cooling system located in Singapore. The simulation results show that the developed optimal design gives the best financial performance. Compared to other conventional cooling system designs, the developed optimized design reduces the life cycle expenses in the range of 7% to 21% and the payback period of about 20%. The study offers a promising techno-commercial optimization tool for the energy-efficient design as well as cost-effective operation of district cooling systems. The variables of the developed tool can conveniently be modified to study the influences of different design and operating parameters.